From Monster-beast to Monster-Person: a Genealogical Study of Monstrosity in Narrative Traditions - Rodríguez Jiménez, Leda (2020)
This article approaches the monstrosity construction, but it mainly aims to narrative fictions. It starts with the genealogical inquiry of the concept teras-monstro to carry on with the topic of metamorphosis: the transformation of the human being in a monster form and the were-wolf as an archetype form. Afterwards, the text turns its attention to the birth of the human monster, not necessarily as a figure derived from animals, but as a person with inner qualities of monstrosity. The arrival of the photographic machine in the middle of the XIX Century was decisive for this change in the representation of the concept.  Finally, the work draws near the importance of Romanticism as cultural-artistic movement, and it’s concerned with the birth of a series of characters that built up and plant the bases for an important part of monstrous figures that we consume in narrative fictions today.